If α , β and γ are roots of equation x 3 + 4 x + 1 .Then, find ( α + β 1 + γ 2 α + β ) + ( β + γ 1 + α 2 β + γ ) + ( γ + α 1 + β 2 γ + α )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution! +1 .....Firstly you got it luckily :p ....Typo: α β + β γ + γ α = 4 and α β γ = − 1 :)
Log in to reply
Lol I first time read it as ( α + β 1 − γ 2 α + β ) and that's why I answered 0 and then saw that the problem was deleted :-)..... Anyways typo in this problem was commited since I was writing a solution to another problem :-)
Hi Abhay Kumar. I am just letting you know you forgot to write " = 0 " in your problem.
Did the same !
Let α + β 1 + γ 2 α + β = γ − 2 = y (as you stated). Then y − 2 = γ and since that is a root of the given function: ( y − 2 ) 3 − y 8 + 1 = 0 multiply by y 3 and simplify: y 3 − 8 y 2 − 8 = 0 . The sum of the roots of this function is 8, which is the desired result.
Same way bud
Relevant wiki: Vieta's Formula Problem Solving - Intermediate
From Vieta's formulas we get: α + β + γ = 0 ⎩ ⎪ ⎨ ⎪ ⎧ α + β = − γ α + γ = − β β + γ = − α ⟹ cyc ∑ ( α + β 1 + γ 2 α + β ) = cyc ∑ γ − 2 = − 2 ( α 1 + β 1 + γ 1 ) x = x 1 ⟹ ( x 1 ) 3 + 4 ( x 1 ) + 1 = 0 ⟹ x 3 + 4 x 2 + 1 = 0 ⟹ α 1 + β 1 + γ 1 = − 4 ⟹ − 2 ( α 1 + β 1 + γ 1 ) = 8
Nice solution (+1) :-)
You can also get the sum of the reciprocals by dividing ab + bc + ca by abc.
Log in to reply
Indeed :),but I wanted to do something different and this method may seem slightly quicker to some people.
Problem Loading...
Note Loading...
Set Loading...
See Vieta's formula α β + β γ + γ α = 4 , α β γ = − 1 α + β + γ = 0 ⟹ α + β = − γ
⎝ ⎜ ⎜ ⎛ − γ α + β 1 + γ 2 α + β − γ ⎠ ⎟ ⎟ ⎞ = γ − 2 The required expression is:-
α − 2 + β − 2 + γ − 2 = = − 2 ( α β γ α β + β γ + γ α ) − 2 × ( − 1 ) 4 = 8